Proses Permukiman Kumuh di Perbatasan Kota: Studi Kasus Perbatasan Kabupaten Badung dengan Kota Denpasar - Graha, I Made Satya; Wedagama, Dewa Ayu Trisna Adhiswari; Wiraatmaja, I Putu Prana (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2024)
Slum settlements usually occur in city centers, but the LC Jatayu Nakula Timur slum settlement is located on the border of Badung Regency and Denpasar City. This research aims to determine the process of slum settlements in city border areas. This research used spatial approach through a qualitative case study method. Primary data was obtained through observation and interviews, while secondary data was obtained from legal sources. The level of slum settlements was identified using the Regulation of The Minister of Public Works and Public Housing No. 14/PRT/M/2018 as a standart, while the spatial growth of slum settlements was analyzed using a geographic information system. Data from interview was used to support the description of spatial growth process. There are two phases of the slum settlement process: Phase I 2012-2016 and Phase II 2017-2022. This research found that there is a growth of slum settlements every year and the development of economic activity from scavengers to stalls and renting uninhabitable housing. The uninhabitable house rentals have unclear legal status of the land tenure.